Experimental study on vertical vibration characteristics of medium-low speed maglev vehicle when standing still on steel beams. (July 2022) - Li, Miao; Chen, Xiaohao; Luo, Shihui; Ma, Weihua; Lei, Cheng; Liu, Wenliang; Gong, Junhu
Levitation stability is the very basis for the dynamic operation of Electromagnetic Suspension (EMS) medium-low speed maglev trains (MSMT). However, self-excited vibration tends to occur when the vehicle is standing still above the lightweight lines, which remains a major constraint to the promotion of medium-low speed maglev technology. In order to study the vertical vibration characteristics of the coupled system of MSMT when it is standing still above lightweight lines, levitation tests were carried out on two types of steel beams: steel beam and active girder of the turnout, with a newly developed maglev vehicle using levitation frames with mid-set air spring. Firstly, modal tests were carried out on the steel beam to determine its natural vibration characteristics; secondly, the acceleration signals and the dynamic displacement signals of the air spring obtained at each measurement point were analyzed in detail in both the time and frequency domains, and the vertical ride comfort was assessed by means of the calculated Sperling index. Subsequently, theoretical explanations were given for the occurrence of self-excited vibration of coupled system from the perspective of the vehicle-to-guideway vibration energy input. Results show that the eigen frequencies of the vehicle on the steel beam and the turnout are 9.65 Hz and 2.15 Hz, respectively, the former being close to the natural frequency of the steel beam while the latter being close to the natural frequency of the air spring suspension system, thus causing the self-excited vibration of the coupled system. It is recommended to either avoid the main eigen frequencies of the coupled system or to increase the damping of the corresponding vibration modes to guarantee a reliable coupled system for its long-term performance. These results may provide valuable references for the optimal design of medium-low speed maglev systems.